The Impact of GLP-1 Receptor Agonists on Body Composition and Musculoskeletal Integrity: A Review of Mechanisms, Protective Strategies, and Clinical Perspectives - Domagała, Szymon; Wiater, Zuzanna; Włodarczyk, Aleksandra; Brankowska, Karolina; Jakubowska, Marta; Olejnik, Michał; Tymińska, Paulina; Górka, Piotr Artur; Frączek, Julia; Kądziołka, Witold (Quality in Sport, 2026)
The emergence of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and dual GIP/GLP-1 agonists has revolutionized obesity pharmacotherapy, enabling weight loss magnitudes of 15–20%, previously attainable primarily through bariatric surgery. A significant clinical challenge, however, is the "muscle gap"—the substantial loss of lean body mass (LBM) observed in pivotal trials. This review provides a critical analysis of the impact of incretin-based therapies on tissue composition, skeletal muscle quality, and functional performance. Drawing on the latest clinical and molecular evidence, we demonstrate that the influence of GLP-1 RAs on skeletal muscle is multidimensional. While absolute muscle mass typically decreases, advanced imaging data suggest an improvement in metabolic muscle "quality" through the reduction of intramuscular fat infiltration and enhanced capillary perfusion. This paper emphasizes that structured exercise - particularly resistance training - and nutritional optimization are not merely supportive measures but essential foundations of therapy required to maintain functional strength and prevent iatrogenic sarcopenia. The review further explores the unique osteoprotective effects of GLP-1 RAs, which safeguard bone mineral density during rapid weight loss, and discusses emerging pharmacological frontiers, including co-pharmacotherapy with myostatin inhibitors and triple agonists like retatrutide. Longitudinal insights from the S-LiTE trial indicate that the sustainability of metabolic benefits post-treatment is heavily dependent on exercise-induced adaptations. We conclude that optimal obesity management requires a multidisciplinary approach where pharmacotherapy serves as an adjunct to structured lifestyle changes, prioritizing functional fitness and long-term musculoskeletal health.